Ρ. Hirst, Gr. Thompson, Globalization in Question. The international economy and the possibilities of Governance - Κ., Η. (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2015)
[Δεν διατίθεται περίληψη / no abstract available]